ETIOLOGY AND MANAGEMENT OF ENDODONTIC FLARE UPS -A SURVEY AMONG DENTAL STUDENTS (Journal of Pharmaceutical Negative Results, 2022)
INTRODUCTION: A flare-up is defined as the occurrence of severe pain and swelling following an endodontictreatment appointment, requiring an unscheduled visit and active treatment. (‘Endodontic flare-ups with periapical lesions’, 2009)Flare-up is a well known complication that disturbs both patients and dentists.An endodontic flare-up is an acute exacerbation of an asymptomatic pulp or periapical pathosis after the initiation or continuation of root canal treatment.(Kaur, 2015)The reported incidence of interappointment flare-ups ranges from 1.4 to 19%. Interappointment flare-ups form a true emergency that requires an unscheduled patient visit and immediate active treatment for pain relief. The aim of this survey was to assess the awareness, knowledge and practice of the endodontic flare ups and its treatment.MATERIALS AND METHOD: An online survey was conducted among 157 undergraduates to evaluate their knowledge in etiology and management of endodontic flare ups among dental students. A convenience sample was taken and the questionnaire was distributed on an online platform. This online questionnaire survey consisted of 14 questions that were distributed to the study population through google forms. The data which was collected was analyzed using Statistical Package for Social sciences (SPSS) software, version 1.0.0.1347 64 bit (IBM Corp., NY, USA). RESULTS: The data were assessed by being subjected to descriptive analysis with the help of frequencies, percentages, means. The data was represented by the means of bar graphs. A Chi-square test was used and results were correlated and associated.Pearson chi square test; value - 146.248, df -12, p value- 0.03 (>0.05). Hence it is proven that the graph is statistically significant. CONCLUSION: This study shows that the dental students are not aware of the etiology and management of the endodontic flare ups. This study helps students to get knowledge about the etiology and management of the dental flare ups and how to handle the situation and how to treat the flare ups.